Crystal structure of (1-methyl-3-(trifluoromethyl)-1H-pyrazol-4-yl)(4-((2-methyl-6-(trifluoromethyl)pyrimidin-4-yl)amino)piperidin-1-yl)methanone, C17H18F6N6O - Pan Nian-Juan; Yan Chang; Fei Qiang; Wu Wen-Neng (Zeitschrift für Kristallographie - New Crystal Structures)
C17H18F6N6O, monoclinic, P21/n (no. 14), a = 9.9491(11) Å, b = 18.1523(17) Å, c = 11.7703(15) Å, β = 113.473(14)°, V = 1949.8(4) Å3, Z = 4, Rgt(F) = 0.0606, wRref(F2) = 0.1876, T = 169.99(10) K.